Consensus document for the kangaroo mother care method - Isabel María Fernández-Medina; Lucía Jiménez-Fernández; Álvaro José Solaz-García; Alicia Llorca-Porcar; Esther Martínez-Miguel; Laura Collados-Gómez (Elsevier, 2024)
Introduction: Currently, kangaroo mother care (KMC) is an intervention whose implementation in clinical practice varies widely. The aim of this document is to gather the latest evidence-based recommendations in an attempt to reduce interprofessional variation and increase the quality of neonatal care. Methods: The document was developed following the guidelines provided in the Methodological Manual for the Development of Clinical Practice Guidelines of the National Health System: formulation and prioritization of clinical questions, literature search, critical reading, development of the document and external review. The target population was preterm (PT) and/or low birth weight (LBW) newborn infants admitted to a neonatal unit. Recommendations: Based on the current evidence, recommendations have been issued to address 18 clinical questions regarding the impact of KMC (morbidity and mortality, physiological stability, neurodevelopment, feeding, pain, families), including infants with vascular access or respiratory support devices. It also describes the KMC procedure (transfer, positioning), the facilitators and barriers related to the implementation of KMC and how to implement KMC in extremely preterm newborns (less than 28 weeks of postmenstrual age in the first days of life). Conclusions: Kangaroo mother care is a beneficial practice for PT infants, LBW infants and their families. The implementation of these recommendations may be useful in everyday clinical practice and may improve KMC outcomes and the quality of care provided to neonatal patients. Resumen: Introducción: Actualmente el método madre canguro (MMC) es una intervención con una alta variabilidad clínica en su aplicación. Este documento ha tenido como objetivo aunar las últimas recomendaciones basadas en la evidencia científica, para intentar disminuir la variabilidad interprofesional e incrementar la calidad de los cuidados al paciente neonatal. Métodos: Se han seguido las directrices descritas en el Manual Metodológico para la elaboración de Guías de Práctica Clínica del Sistema Nacional de Salud: redacción y priorización de preguntas clínicas, búsqueda bibliográfica, lectura crítica, elaboración del documento y revisión externa. La población a la que se dirige son los recién nacidos pretérmino (RNPT) y/o de bajo peso (RNBP) ingresados en una unidad neonatal. Recomendaciones: En base a la evidencia existente, se proponen recomendaciones para 18 preguntas clínicas sobre el impacto del MMC (morbimortalidad, estabilidad fisiológica, dolor, neurodesarrollo, alimentación, dolor, familias), incluyendo a los portadores de dispositivos venosos o respiratorios. También recoge el procedimiento del MMC (transferencia, postura), los facilitadores y barreras para su implantación y su aplicación en prematuridad extrema (menores de 28 semanas de gestación en los primeros días de vida) Conclusiones: El método madre canguro es una práctica beneficiosa para los RNPT, RNBP y sus familias. El uso de las recomendaciones aportadas podrá ayudar en la práctica clínica diaria y quizás se consiga mejorar los resultados del método madre canguro y la calidad de los cuidados prestados al paciente neonatal.